2014
DOI: 10.1136/oemed-2013-101659
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use and incident diabetes among wives of farmers in the Agricultural Health Study

Abstract: Objective To estimate associations between use of specific agricultural pesticides and incident diabetes in women. Methods We used data from the Agricultural Health Study, a large prospective cohort of pesticide applicators and their spouses in Iowa and North Carolina. For comparability with previous studies of farmers, we limited analysis to 13,637 farmers’ wives who reported ever personally mixing or applying pesticides at enrollment (1993-1997), who provided complete data on required covariates and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 31 publications
1
72
2
1
Order By: Relevance
“…Over the past years, pesticides, as well as other environmental factors, have been indicated as possible co-factors in the pathogenesis of DM (6668) (Table III). A systematic review analysed the link between pesticides, DM, and diabetes-related pathologies (69), based on the increasing prevalence of both DM2 and the use of pesticides in Asia.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Over the past years, pesticides, as well as other environmental factors, have been indicated as possible co-factors in the pathogenesis of DM (6668) (Table III). A systematic review analysed the link between pesticides, DM, and diabetes-related pathologies (69), based on the increasing prevalence of both DM2 and the use of pesticides in Asia.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Over 20 cross-sectional studies in highly exposed and background-exposed populations have reported positive associations of blood or adipose concentrations of dioxins Several longitudinal studies have also reported positive associations of PCB [71][72][73], dioxin [10,74] and/or organochlorine [12,72,[75][76][77][78] concentrations with T2DM, while some studies reported no associations with certain POPs [78][79][80]. Among Vietnam War veterans who were involved in spraying Agent Orange, T2DM risk increased with serum TCDD concentrations [10,74].…”
Section: Evidence For An Association With T2dmmentioning
confidence: 94%
“…In a prospective study of farmers and their spouses in the USA, self-reported ever-use of the organophosphates coumaphos, phorate, terbufos and trichlorfon were associated with increased risk of incident diabetes (adult-onset, unspecified type) in men [75], and fonofos, parathion and phorate ever-use were associated with incident diabetes in women [76]. Additionally, the organophosphates phorate and diazinon were associated with gestational diabetes among women in the AHS who reported any pesticide use during the first trimester of pregnancy [134].…”
Section: Evidence For An Association With T2dmmentioning
confidence: 97%
See 1 more Smart Citation
“…Exposure to pesticides has been linked to deleterious health effects for agricultural workers, 1–7 including delayed neuropathy, 7 DNA damage and mutations, 8 thyroid disease, 9 diabetes, 10,11 Parkinson’s disease,- 7,12 and several cancers. 13,14 Two of the most commonly used pesticides in North Carolina tobacco production 15 are carbaryl and pendimethalin.…”
Section: Introductionmentioning
confidence: 99%